2014
DOI: 10.1016/j.optcom.2014.03.056
|View full text |Cite
|
Sign up to set email alerts
|

Polarization entangled photon-pair source based on quantum nonlinear photonics and interferometry

Abstract: International audienceWe present a versatile, high-brightness, guided-wave source of polarization entangled photons, emitted at a telecom wavelength. Photon-pairs are generated using an integrated type-0 nonlinear waveguide, and subsequently prepared in a polarization entangled state via a stabilized fiber interferometer. We show that the single photon emission wavelength can be tuned over more than 50 nm, whereas the single photon spectral bandwidth can be chosen at will over more than five orders of magnitud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 63 publications
1
33
0
Order By: Relevance
“…It should be mentioned that, in this configuration, only non-degenerate photon pairs can be exploited, as the pump laser light needs to be rejected to avoid detector saturation. Finally, a group in Kanagawa (Japan), and our team demonstrated that energy-time entanglement can be converted to polarization entanglement by a properly engineered polarization dependent delay line [131][132][133]. As shown in FIG.…”
Section: B Hybrid Polarization Entanglement Sourcesmentioning
confidence: 91%
See 1 more Smart Citation
“…It should be mentioned that, in this configuration, only non-degenerate photon pairs can be exploited, as the pump laser light needs to be rejected to avoid detector saturation. Finally, a group in Kanagawa (Japan), and our team demonstrated that energy-time entanglement can be converted to polarization entanglement by a properly engineered polarization dependent delay line [131][132][133]. As shown in FIG.…”
Section: B Hybrid Polarization Entanglement Sourcesmentioning
confidence: 91%
“…Our group took also advantage of the high SPDC efficiency of type-0 PPLN/Ws to demonstrate a hybrid polarization entanglement source achieving bandwidths of 0.2 pm and 4 pm at 1560 nm. Near perfect visibilities of 99% and 97%, respectively, have been achieved in the standard Bell inequality test [132,133]. The 0.2 pm source was further used to perform a continuous wave teleportation experiment [84], and the 4 pm source was an essential building block for testing the foundations of quantum physics in a quantum delayed-choice experiment showing wave-particle complementarity [7].…”
Section: E Advanced Photonic Entanglement Sourcesmentioning
confidence: 99%
“…. A continuous‐wave (CW) laser at 769.88 nm (TOPTICA DL Pro) pumps a periodically poled lithium niobate waveguide (PPLN/WG) for generating broadband energy‐time entangled pairs of photons via SPDC . We exploit energy‐time entangled photons as information carriers, due to their inherent invulnerability against polarization mode dispersion and drifts , making this approach more robust for long distance distribution.…”
Section: Experimental Section and Methodsmentioning
confidence: 99%
“…Polarization matching is simply obtained by inserting a fibre polarization controller on the LO path. A home-made fibre stretcher implements the LO phase scanning [27]. At the 50:50 f-BS outputs, light is directly sent to two InGaAs photodiodes (Thorlabs, FGA10, without cap) showing each η d ≈ 0.88 quantum efficiency at 1542 nm.…”
mentioning
confidence: 99%